2006
DOI: 10.1038/sj.onc.1209979
|View full text |Cite
|
Sign up to set email alerts
|

Distinct promoters mediate constitutive and inducible Bcl-XL expression in malignant lymphocytes

Abstract: Bcl-X L is a Bcl-2-related survival protein that is essential for normal development. Bcl-X L expression is rapidly induced by a wide range of survival signals and many cancer cells constitutively express high levels. The Bcl-X gene has a complex organization with multiple promoters giving rise to RNAs with alternate 5 0 non-coding exons. Here we have investigated the mechanisms that control basal and induced expression of Bcl-X L in B-lymphoma cells. Antisense experiments demonstrated that Bcl-X L was essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…(Top) The distal (IB) and proximal (IA) non-coding exons, and part of the first coding exon (II) including the translational start site (ATG). Additionally, the three described BCL2L1 promoters (p1B, p1A, p2) are depicted [ 17 ]. (Bottom) Major BCL2L1 transcripts starting from promoter p1B or p1A, comprising exon IB or IA, respectively, or starting upstream from exon II.…”
Section: Resultsmentioning
confidence: 99%
“…(Top) The distal (IB) and proximal (IA) non-coding exons, and part of the first coding exon (II) including the translational start site (ATG). Additionally, the three described BCL2L1 promoters (p1B, p1A, p2) are depicted [ 17 ]. (Bottom) Major BCL2L1 transcripts starting from promoter p1B or p1A, comprising exon IB or IA, respectively, or starting upstream from exon II.…”
Section: Resultsmentioning
confidence: 99%
“…1), we asked whether such up-regulation was at the mRNA level. The bcl-X gene contains multiple promoters, and its transcription may generate several splice variants [4042]. The main Bcl-xL transcript is termed in the rat “transcript variant 3” and codes for protein isoform 2 with molecular mass of approximately 26 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we found an increase in the pancreatic level of not only the main transcript but also an alternative splice variant from the bcl-X gene. Transcriptional regulation of this gene [4042] has not been studied in pancreatitis. One regulator of Bcl-xL gene expression in a number of cell types is the transcription factor NF-κB [41].…”
Section: Discussionmentioning
confidence: 99%
“…The Bcl-X promoter region is complex because it contains different promoters that generate different 5Ј noncoding exons and different proportions of Bcl-X L and Bcl-X S mRNAs (15)(16)(17)(18). It has been previously demonstrated that various nuclear factors including NFB, STAT, Ets, Ikaros, and steroid hormones activate Bcl-X transcription acting on its different promoters in various cell types (15, 17, 18, 26 -28).…”
Section: Discussionmentioning
confidence: 99%